La interculturalidad en el proceso de enseñanza-aprendizaje en la unidad educativa Abdón calderón en el período 2016-2017. - Barreno Faz, Cristian Aníbal (2019)
The research problem arose with the observation of a deficient cultural identity, ignorance of the intercultural manifestations and foreignerism practiced by the students of the Educational Unit "Abdón Calderón Muñoz" that are the result of the execution of pedagogical processes planned by teachers without taking into account adequate methodological strategies for the development of intercultural knowledge, its acceptance and respect. This has caused that education is not inclusive and equitable in its entirety, which limits the development and formation of the individual cultural identity and makes the institutional coexistence not harmonious. Hence the importance of this research, since its purpose is for the educational community to understand the main definitions and foundations related to interculturality which leads to the strengthening of a harmonious coexistence between the different ethnic groups that exist in the educational environment. In order to determine the incidence of interculturality in the teaching-learning process, field research was developed through the empirical method with a quantitative approach since the data obtained through the surveys applied to teachers and students were tabulated and represented in tables and statistical tables. The results of this research were analyzed and interpreted so that it could be concluded that the majority of students do not identify or value the ethnic and cultural diversity of the country, because the teachers show little interest in this topic and when planning, executing and evaluating educational processes, they do not propose activities that favor the development and strengthening of ethnic cultural knowledge so that it is recommended to implement self-management actions in the Educational Unit to organize, execute and participate in refresher courses in terms of interculturality implementation in the teaching-learning processes and evaluation activities in order to raise awareness among teachers about the importance of developing and promoting knowledge of the different cultural manifestations in the students, contributing favorably to their academic achievement, personal training and professional future development profess.